Virtual reality and travel anxiety during the COVID-19 pandemic: the moderating role of blockade intensity - Wang, Qingjin; Shi, Renbo; Zhang, Kaiyun; Liu, Xiao (Frontiers in Psychology, 2024)
The COVID-19 pandemic has deprived travelers of the right to continue their travel or leisure activities, while creating concerns about the safety of travel. In view of the great impact of the COVID-19 pandemic on travelers, we discussed the impact of virtual reality on travel anxiety during the COVID-19 pandemic, and considered the regulatory effect of blockade intensity. In order to explore the relationship between virtual reality and travel anxiety in depth, this study conducted a questionnaire survey on 299 Chinese tourists who had experienced virtual reality activities related to travel, and empirically analyzed the questionnaire data using SPSS 26 software. The results show that virtual reality has a significant negative effect on travel anxiety during the COVID-19 pandemic, i.e., virtual reality technology can provide a safer virtual travel experience for people and reduce their travel anxiety. At the same time, the relationship between virtual reality and travel anxiety varied to some extent depending on the intensity of the lockdown in each region, with the mitigating effect of virtual reality on travel anxiety being enhanced by high levels of lockdown. Therefore, we believe that although lockdown policies are necessary for some time to come, travel companies need to make further efforts to provide more convenient virtual reality services to alleviate travel anxiety caused by COVID-19 pandemic and lockdown to tourists. At the same time, virtual reality opens up new ideas for travel businesses under the impact of COVID-19 and contributes to the sustainable development of the travel industry.